The Roles of Family Support in Child’s Emotional Development in Inside Out Film (2015) - Gusti Amelia; Minsakutra Minsakutra; Tira Mariana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study examines the role of family support in a child’s emotional development as portrayed in the film Inside Out (2015). The aims of this research are to identify the emotional development experienced by the main character, Riley, to analyze the types of family support depicted in the film, and to examine the role of family support in her emotional development. This research uses a qualitative descriptive method with a psychological approach. The theoretical framework is based on Berk’s (2018) theory of emotional development and Friedman et al.’s (2021) theory of family support. Data were collected through documentation by analyzing selected scenes and dialogues that represent Riley’s emotional experiences and family interactions. The findings show that Riley experiences several aspects of emotional development, including self-conscious emotions, emotional understanding, and emotional self-regulation, especially during her adjustment to a new environment after relocation. In addition, the film portrays three types of family support: emotional support, informational support, and appraisal support. The results indicate that family support plays a significant role in Riley’s emotional development by helping her develop emotional awareness, strengthen emotional understanding, and improve emotional regulation in dealing with challenging situations.